2008
DOI: 10.1001/archotol.134.6.621
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Olfactory Function With Changes in the Volume of the Human Olfactory Bulb

Abstract: To investigate changes of olfactory bulb (OB) volume over time in relation to olfactory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 21 publications
5
83
0
2
Order By: Relevance
“…2,19 The correlation of olfactory function with volume of the human OB has been established. 24,37 In this study, a positive correlation between olfactory deficit and OB volume was found both in patients with PD and controls. It may be that olfactory dysfunction in PD is related to loss of olfactory neurons or disrupted input to the OB.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…2,19 The correlation of olfactory function with volume of the human OB has been established. 24,37 In this study, a positive correlation between olfactory deficit and OB volume was found both in patients with PD and controls. It may be that olfactory dysfunction in PD is related to loss of olfactory neurons or disrupted input to the OB.…”
Section: Discussionsupporting
confidence: 62%
“…The bilateral volume of the OB and the depth of the OS were measured in all study subjects. Because there may be differences between left-and rightsided OB volumes and OS depth, [22][23][24] we used the maximum volume of the OB and depth of the OS in each individual for the analysis. The OB volume was expressed in cubic millimeters by calculating the inplane area and the thickness of the OB.…”
Section: Imaging Data Analysesmentioning
confidence: 99%
“…Given that a larger olfactory bulb volume is indicative of better olfactory function (Haehner et al, 2008), it is possible that the volume of the bulb directly relates with the functional needs and therefore the behavioral ecology of the above species.…”
Section: Discussionmentioning
confidence: 99%
“…If the connection between depression and olfaction is a temporal phenomenon that disappears after remission of depression, OB volume could also be hypothesized to recover after successful psychotherapy. Volumetric changes of the OB are described in several studies in humans both in connection to peripheral Haehner et al 2008)) or central disorders (Hummel et al 2013b;Turetsky et al 2000Turetsky et al , 2003Yousem et al 1998Yousem et al , 1999. However, studies provide contradictory information on the potential for neurogenesis either within the OB or through progenitor cells derived from the sub-ventricular zone (SVZ) through the rostral migratory stream (RMS) (see (Bergmann et al 2012;Huart et al 2013;Lotsch et al 2013) for ongoing debate).…”
Section: Introductionmentioning
confidence: 99%